Islamic Republic of Afghanistan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper provides a preliminary view on Afghanistan's external competitiveness through a review of some macroeconomic, microeconomic, and institutional indicators. It discusses the rebuilding of domestic revenue, and analyzes the macroeconomic impact of the drug economy and the counternarcotics efforts. The paper provides, whenever available, statistical information on the real, fiscal, monetary, and external sectors. It also contains a list of state-owned enterprises and an updated summary of the tax system as of end-December 2005.